2013
DOI: 10.1021/jp311641g
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Control of Metal Loading and Composition of Carbon Aerogel Supported Pt–Cu Alloy Nanoparticles by Supercritical Deposition

Abstract: Carbon aerogel (CA) supported Pt−Cu bimetallic nanoparticles were synthesized via simultaneous adsorption of bis(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…All of the peaks associated with the crystal planes of CuO formed after the O2 activation at 800 °C , shifted to higher 2θ values upon reaction with CH4 at 200 °C . This could be associated with the contraction of the crystal lattice 58 by the chemisorption of reaction intermediates on CuO. Upon subsequent extraction in H2O (Step G1) which removed the chemisorbed intermediates by the formation of methanol, the XRD showed that the peaks shifted back to their original values obtained after the O2 activation step however with lower intensity.…”
Section: 2catalyst Characterizationmentioning
confidence: 98%
“…All of the peaks associated with the crystal planes of CuO formed after the O2 activation at 800 °C , shifted to higher 2θ values upon reaction with CH4 at 200 °C . This could be associated with the contraction of the crystal lattice 58 by the chemisorption of reaction intermediates on CuO. Upon subsequent extraction in H2O (Step G1) which removed the chemisorbed intermediates by the formation of methanol, the XRD showed that the peaks shifted back to their original values obtained after the O2 activation step however with lower intensity.…”
Section: 2catalyst Characterizationmentioning
confidence: 98%
“…Furthermore, the relatively low critical temperature (Tc = 31 • C) and pressure of scCO 2 (pc = 73.8 bar), make its handling straightforward, employing standard high pressure technology [110]. Seminal contributions for the preparation of bimetallic NPs by this approach pioneered by the groups of Erkey [111][112][113][114][115] and Wai [116,117], opened new opportunities towards the preparation of tailored nanomaterials with high potential in catalysis by the impregnation of the solutes into finely organized architectures. In particular, this synthetic methodology consists of three main steps: dissolution of a metal complex in a supercritical fluid, followed by its sorption or adsorption onto a support, and its final transformation to a zero-valent metal species [111].…”
Section: Synthesis Of Bmnps In Supercritical Fluidsmentioning
confidence: 99%
“…Cu-Cu2O core-shell nanoparticles were synthesized when the carbon aerogel-CuDI6 composites were treated with H2 at 250 °C, while phase segregated Cu-Cu2O nanoparticles were obtained when an O2 treatment at 160 °C preceded the H2 treatment at 300 °C [112]. Later reports from Erkey et al describe the preparation of carbon aerogel supported Pt-Cu BMNPs via the simultaneous adsorption of the polyfluorinated copper precursor CuDI6 and dimethyl(1,5-cyclooctadiene)platinum(II) onto carbon aerogels in scCO2, followed by thermal conversion at ambient pressure [114]. Homogeneously dispersed Pt-Cu NPs were formed at the carbon aerogel surface through thermal decomposition of the precursors at 400 °C.…”
Section: Synthesis Of Bmnps In Supercritical Fluidsmentioning
confidence: 99%
“…Recent reports showing that the adsorption behavior of organometallic compounds in supercritical fluids follows equilibrium adsorption isotherms. [66] Given the 20 hours allowed for adsorption, it is likely that the amount adsorbed corresponds to equilibrium concentrations established between the surface and the fluid phase. Silver nitrate tests did not indicate any significant residual chloride following deposition of platinum and calcination.…”
Section: Catalyst Compositionmentioning
confidence: 99%